Spinocerebellar ataxia type 2 with glial cell cytoplasmic inclusions. Issue 3 (13th February 2004) - Probst-Cousin, S; Acker, T; Epplen, J T; Bergmann, M; Plate, K H; Neundörfer, B; Heuss, D
Abstract : Glial cell cytoplasmic inclusions were identified in a case of spinocerebellar ataxia type 2. These have not been reported before. The inclusions were found in low frequency in the dentate nucleus, cerebellar white matter, pontine transverse fibres, and the inferior olivary nucleus. They were of variable size and shape and expressed ubiquitin, thus resembling glial cytoplasmic inclusions in multiple system atrophy. However, their immunohistochemical profile was different as they did not show immunoreactivity for either tau protein or α-synuclein. There was no evidence of expanded polyglutamine tracts in these inclusions, which also failed to label with silver stains. As in many other neurodegenerative diseases, in spinocerebellar ataxia type 2 there may be pathogenic contributions of glial cells other than the common astrogliotic response to neuronal damage.